Maize Milling By-Products: From Food Wastes to Functional Ingredients Through Lactic Acid Bacteria Fermentation - Pontonio, Erica; Dingeo, Cinzia; Gobbetti, Marco; Rizzello, Carlo Giuseppe (Frontiers in Microbiology, 2019)
Although recognized as important sources of functional compounds, milling by-products are often removed from the cereal kernel prior milling process. Indeed, the high presence of fiber in bran and the co-presence of lipids and lipase in germ are often considered as downsides for breadmaking. In this work, Lactobacillus plantarum T6B10 and Weissella confusa BAN8 were used as selected starters to ferment maize milling by-products mixtures made with heat-treated or raw germ and bran. The effects on the biochemical and nutritional features as well as the stability of the milling by-products were investigated. Lactic acid bacteria metabolisms improved the free amino acids and peptides concentrations and the antioxidant activity and caused a relevant phytic acid degradation. Moreover, fermentation allowed a marked decrease of the lipase activity, stabilizing the matrix by preventing oxidative processes. The use of fermented by-products as ingredients improved the nutritional, textural and sensory properties of wheat bread. Fortified breads (containing 25% of fermented by-products) were characterized by a concentration in dietary fiber and proteins of ca. 11% and 13% of dry matter, respectively. Compared to the use of the unfermented ones, the addition of pre-fermented by-products to bread caused a significant increase in protein digestibility (up to 60%), and a relevant decrease of the starch hydrolysis index (ca. 13%). According to the results, this study demonstrates the potential of fermentation to convert maize bran and germ, commonly-considered food wastes, into nutritive improvers, meeting nutritional and sensory requests of modern consumers.